The Influence of TikTok Use on Religious Character and Religious Obedience of Students - Aisah Luthfiatur Rohimy; Imam Junaris (CV. Gerasi Insan Nusantara, 2026)
The development of information technology and social media in the digital era that has various impacts on the lives of adolescents, especially in the formation of religious character and worship obedience. The TikTok application as one of the popular social media has the potential to influence student behavior and mindset. This study aims to determine the influence of TikTok social media use on students' religious character and worship obedience. The research uses a quantitative approach with a correlational type. The research population was 355 students in class X of SMA Negeri Mojoagung Jombang, with a sample of 80 respondents determined using the Slovin formula and purposive sampling techniques. Data collection was carried out through the distribution of google form questionnaires to respondents as well as documentation to support research data. The research data were analyzed using Pearson correlation tests and simple linear regression with the help of IBM SPSS version 25. The results showed that TikTok social media use had a positive and significant relationship with religious character (r = 0.553; Sig. = 0.000) and student worship obedience (r = 0.511; Sig. = 0.000). In addition, the results of the regression test showed that TikTok use had a significant effect on religious character (F = 34.306; Sig. = 0.000) and worship obedience (F = 27.618; Sig. = 0.000). Thus, the use of TikTok has a positive and significant effect on religious character and religious obedience of students even though it is also influenced by other factors.